2018
DOI: 10.2196/10090
|View full text |Cite
|
Sign up to set email alerts
|

User-Driven Comments on a Facebook Advertisement Recruiting Canadian Parents in a Study on Immunization: Content Analysis

Abstract: BackgroundMore people are searching for immunization information online and potentially being exposed to misinformation and antivaccination sentiment in content and discussions on social media platforms. As vaccination coverage rates remain suboptimal in several developed countries, and outbreaks of vaccine-preventable diseases become more prevalent, it is important that we build on previous research by analyzing themes in online vaccination discussions, including those that individuals may see without activel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
4
44
0
2
Order By: Relevance
“…For instance, Basch et al (2017), Donzelli et al (2018) and Porat et al (2018) report high online prevalence and popularity of autism-related discussions in fora on vaccination. Tustin et al (2018) and Xu and Guo (2018) also reported widespread misinformation about side effects, as well as mistrust in government or pharmaceutical companies in discussions on vaccination. Krishna's (2017) study of active propagators of these messages found that those who were knowledge-deficient and vaccine-averse exhibit higher levels of activity than those who are not.…”
Section: Vaccines and Communicable Diseasesmentioning
confidence: 99%
“…For instance, Basch et al (2017), Donzelli et al (2018) and Porat et al (2018) report high online prevalence and popularity of autism-related discussions in fora on vaccination. Tustin et al (2018) and Xu and Guo (2018) also reported widespread misinformation about side effects, as well as mistrust in government or pharmaceutical companies in discussions on vaccination. Krishna's (2017) study of active propagators of these messages found that those who were knowledge-deficient and vaccine-averse exhibit higher levels of activity than those who are not.…”
Section: Vaccines and Communicable Diseasesmentioning
confidence: 99%
“…Facebook users who showed negative feelings about vaccines are introduced as a "pro-science" group that tries to give information about vaccines that is supposedly being hidden [18]. Tustin et al [19] revealed that the comments of this social network mostly speak about distrust towards pharmacists or healthcare providers and include negative experiences with vaccines. These studies are based on the new advertising tool from Facebook, in which anti-vaccination ads have been included talking about alleged institutional fraud and promoting vaccination [20].…”
Section: Facebook and Youtube And Vaccine Infringementmentioning
confidence: 99%
“…In terms of interaction, comments in favor of immunization receive more "likes" than those against [21], although the latter group consumes more content [22]. As on Twitter, antivaccine users based their posts and comments on personal stories, vaccines risks, vaccine components, distrust in pharmaceutical industry and conspiratory theories [18][19][20][21][22]. Even though pro-vaccine users and posts have more presence, anti-vaccine users seems to grow more cohesively on Facebook than pro-vaccine groups [22].…”
Section: Facebook and Youtube And Vaccine Infringementmentioning
confidence: 99%
“…2,4,5 Amongst the barriers to universal vaccination, misinformation regarding the benefits, medicinal composition, and adverse effects of vaccination limits patient understanding and overall buy-in. 6 As patients increasingly consult the Internet and peer networks, such as those generated on social media, for health information, growing interest has emerged in the role of interactive social media in public health promotion. [7][8][9][10] However, there is also substantial potential for harmful misinformation to spread across networks which may be propagated via the contemporary anti-vaccination movement, fueling vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%